Pertanggungjawaban Tim e-sport Terkait Hak Upah Atlet Profesional (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the legal responsibilities of e-sports teams regarding the fulfillment of wage rights and the forms of legal protection for professional athletes based on applicable laws and regulations in Indonesia. As the e-sports industry develops as part of the digital and creative economy, the issue of employment relations between e-sports teams (as employers) and athletes (as professional workers) has become an important issue that requires in-depth study from a legal perspective. This study uses a normative legal method with a statutory approach. This approach is used to analyze positive legal norms that regulate the rights and obligations in employment relations and the legal protection mechanisms available to e-sports athletes. This research is prescriptive in nature, meaning it not only describes the applicable legal conditions but also provides recommendations for improvements. The legal material collection technique was carried out through a literature study that included relevant laws and regulations, books, scientific journals, and court decisions. The results of the study indicate that e-sports teams, which can legally be in the form of business entities or corporations, have a legal obligation to pay athletes' wage rights in a timely and full manner as stated in the employment contract. If there are delays or deductions in wages without legal basis, e-sports teams can be held liable under civil, criminal, and administrative laws. Furthermore, legal protection for athletes as workers still faces various challenges, particularly related to weak oversight by relevant authorities and low levels of legal awareness among both team management and athletes themselves. To address this, concrete steps are needed in the form of strengthening law enforcement mechanisms, increasing legal education for e-sports industry players, and developing labor protection policies specifically for e-sports. This way, the rights of professional athletes can be guaranteed fairly and proportionally.